2006
DOI: 10.1097/01.mlr.0000208195.83749.c3
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Racial and Ethnic Disparities in Health Care

Abstract: Researchers and policymakers may need to broaden the scope of factors they consider as barriers to access if the goal of eliminating disparities in health care is to be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(169 citation statements)
references
References 17 publications
7
157
1
4
Order By: Relevance
“…Previous studies have found that socioeconomic differences such as insurance status explained a significant portion of the general health disparities that exist among racial/ethnic minorities. 2,3 Specifically among patients with diabetes, healthcare access and insurance status have been shown to explain some, but not all, of the disparities in glucose control among Latinos. 4,5 Asian…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that socioeconomic differences such as insurance status explained a significant portion of the general health disparities that exist among racial/ethnic minorities. 2,3 Specifically among patients with diabetes, healthcare access and insurance status have been shown to explain some, but not all, of the disparities in glucose control among Latinos. 4,5 Asian…”
Section: Introductionmentioning
confidence: 99%
“…10 Although many of the differences in health and health care use are related to differences in socioeconomic factors and access to care, most research has found that racial-ethnic disparities persist even after adjustment for these factors. [1][2][3][4][5]8,11,12 Elimination of racial-ethnic health care disparities requires action on multiple levels of health care organization and delivery. The IOM's report, "Unequal Treatment: Confronting Racial and Ethnic Disparities in Health Care," makes recommendations aimed at the health care system or institutional level.…”
Section: Introductionmentioning
confidence: 99%
“…Although the original applications explored wage differentials across groups the method can be applied to understand why two groups have differences in a wide range of outcome variables, including health variables (Kirby, Taliaferro, and Zuvekas 2006;Powell et al 2012). In our context, we compare individuals in the top and bottom halves of the empirical distribution of our sample of school-leaving state unemployment rates.…”
Section: Mechanismsmentioning
confidence: 99%